APLIKASI MEMO ONLINE (E-MEMO) LABORATORIUM TEKNIK INFORMARTIKA BERBASIS ANDROID - Robby Nugraha; Ivan Maurits; M Achsan Isa Al Anshori (Asosiasi Dosen Muda Indonesia, 2023)
Practicum is one of the academic activities that must be carried out by students at Gunadarma University. It's not just one department that does practicums, but all majors do practicums. One of the practicums that students must do is the Informatics Engineering Laboratory which is intended for students of the Faculty of Industrial Technology. In practicums in several majors, including practicum in the Informatics Engineering Laboratory, if the practitioner does not take part in the practicum for any reason, except for getting a special case, they must make a memo as the practitioner's identity to take part in the practicum again. To make a memo, the practitioner must come to the Informatics Engineering Laboratory Staff room to make a memo. The practitioner can make memos if the practitioner follows the specified time to make memos. Not only does the memo maker have to comply with the time the memo is written, but taking memos also must comply with the time the memo is taken. It can take quite a long time to get the memo because you have to come on time to the Informatics Engineering Laboratory Staff room and wait to pick up the memo. Therefore, the author took the initiative to create a mobile application called